Implementation of Al-Quran Learning with the Ummi Method for Students with Special Needs in Elementary Schools - Agustina Putri Subatas; Nur Maslikhatun Nisak (Universitas Muhammadiyah Sidoarjo, 2023)
This research is backgrounded by the lack of understanding of Qur'anic learning in students with special needs who should get the right learning and easy to understand. The objectives of this study are: (1) Analyzing the implementation of Qur'an learning with ummi technique for students with special needs at SD Muhammadiyah 2 Tulangan; (2) analyze the obstacles in the implementation of Qur'anic learning with the Ummi Method in students with special needs and (3) analyze the advantages and disadvantages of applying Qur'an learning with the Ummi Method at SD Muhammadiyah 2 Tulangan. The research method used is descriptive qualitative. The techniques used are Interview techniques, observation, documentation